Investigation of non-ideal gas flows around a circular cylinder. (1st April 2023) - Matar, Camille; Cinnella, Paola; Gloerfelt, Xavier; Reinker, Felix; aus der Wiesche, Stefan
Abstract: The aerodynamic performance of a cylinder Pitot probe for velocity measurements in compressible non-ideal gas flows, such as those encountered in Organic Rankine Cycle (ORC) turbines, is investigated by means of Computational Fluid Dynamics. Numerical simulations are performed at subsonic and transonic conditions, and freestream Reynolds numbers are in the cylinder critical regime. The working fluid is the organic vapour Novec™ 649. Air flow simulations at similar inlet conditions are reported for comparison. Steady and unsteady RANS solutions are computed with the Spalart–Allmaras turbulence model. The results are assessed against experimental measurements collected in a wind tunnel. URANS is in good agreement with experimental data for all considered conditions, and delivers reasonably accurate estimations of the cylinder back pressure. Using a dense gas leads to a lower minimum pressure coefficient compared to air, alongside a reduced maximum Mach number due to the non-ideal speed of sound behaviour. In the experimentally studied range of compressibility factors and Mach numbers, discrepancies observed with respect to air flow are mostly an effect of the different isentropic exponents. In the transonic regime, shock waves causing boundary layer separation are weakened in the dense gas, but back pressure is also decreased, contributing to rising form drag. Highlights: In subsonic regimes, weakly non-ideal conditions essentially do not affect the flow. The back pressure prediction is improved by URANS over RANS for transonic conditions. Strongly non-ideal thermodynamic conditions cause the gas to expand more. In diluted conditions, differences between flows are due to the isentropic exponent.